A Study of Fund Characteristics and Fund Performance in Malaysia - S.W Chong, Venny; M. Lai, M; L. Chong, L (International Journal of Engineering and Technology, 2018)
This study examines the relationship between fund characteristics and fund performance in Malaysia mutual fund from January 2001 to December 2014.Â A total of 543 sample funds are employed. Systematic risk (beta), turnover ratio, expense ratio, fund size, fund objective, fund age and fund type served as the fund characteristics. Jensenâ€™s alpha on capital assets pricing model (CAPM) was the indicator of the fund performance. The results indicated that conventional funds tend to have higher trading activities than Islamic funds. The ordinary least squares regression results indicated that turnover ratio, fund age, lagged expense, lagged fund size has significant relationship with fund performance. However, risk, expense ratio, size, fund objective, fund types showed no relationship with Jensenâ€™s alpha performance.Â Overall, the results suggested that there are several specific fund characteristics lead to differences in fund performance. The results provided significant implications for the fund investors and fund management companies on their investment decisions.Â